EVALUASI DAMPAK PEMBERDAYAAN MASYARAKAT DALAM RANGKA PENGEMBANGAN WILAYAH DI KABUPATEN SEMARANG - Soebandriyo Soebandriyo; Mursid Zuhri; Mulatto Mulatto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2009)
The objective of this research are to identify the ness enable from which have been carry out, to conduct the aid evalution which has been given, to give recommendation for local government compiling strategy of development of Program Pengembangan Kecamatan (PPK) in Semarang. Regency. The type of this research is description research. The result of this research are : (1) Through the program pemberdayaan masyarakat that have various activities gave social economic impact positively for area development;(2) Although the PPK in generally have given positive effect, but relatively there are the less result in treatment after project, that couse the recipient did not solute the arise problem carried aut;(3) From various actifities that carried out the most developety is the actifities direct need to the society, with the low grade difficulty;(4) Imitation aspect of PPK is determined by difficulty grade, especially in dealing with tech, nical skill, material, and fund.